2016
DOI: 10.9778/cmajo.20150107
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in the outcomes of peripheral arterial disease: a population-based cohort study

Abstract: We identified no significant differences in the composite risk of major adverse cardiovascular events between women and men with PAD, although our findings suggest men may be at increased risk for adverse limb events compared with women. Cardiovascular health campaigns should focus on both women and men to promote early diagnosis and management of PAD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 34 publications
2
16
0
1
Order By: Relevance
“…Our findings are consistent with a contemporary population-based study from Canada reporting that a similar proportion of patients received statin treatment (w60%), but there was a better adherence to ACE inhibitors (w70%). 12 When examining the initiation of these drugs in relation to timing of the PAD diagnosis (Fig 1), it was unclear whether it was the physicians in the hospital or in primary care who initiated the therapy, as the proportion of patients receiving therapy increased up to 3 months after the PAD diagnosis. The uncertainty about responsibilities for drug treatment initiation between specialist and primary care is unfortunate and may explain the low percentage of primary PAD patients receiving adequate secondary medical treatment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our findings are consistent with a contemporary population-based study from Canada reporting that a similar proportion of patients received statin treatment (w60%), but there was a better adherence to ACE inhibitors (w70%). 12 When examining the initiation of these drugs in relation to timing of the PAD diagnosis (Fig 1), it was unclear whether it was the physicians in the hospital or in primary care who initiated the therapy, as the proportion of patients receiving therapy increased up to 3 months after the PAD diagnosis. The uncertainty about responsibilities for drug treatment initiation between specialist and primary care is unfortunate and may explain the low percentage of primary PAD patients receiving adequate secondary medical treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the patients studied were considerably older and demonstrated a higher CV disease burden than is commonly observed in randomized controlled trials and quality registers. 4,12 In our study, we have identified a unique population, patients with their first PAD diagnosis in a specialist setting at a nationwide level. This population of patients has previously not been well described and clearly shows that for many PAD patients, the first clinical manifestation of atherosclerotic disease is limb symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In several observational studies for critical limb ischemia, surgical outcomes defined as MACE (including death), amputation, and a second intervention were identical for both sexes [61,62]. However, Lejay et al published their retrospective data in 2015 concluding that women were at higher risk of adverse events [63]. This may be attributed to the older age of women enrolled in this cohort.…”
Section: Surgical Interventionmentioning
confidence: 92%
“…Women with PAD have a two- to fourfold increased risk of cardiovascular mortality and morbidity compared to women without PAD [ 15 ]. Compared to men, women are more likely to be admitted for acute myocardial infarction [ 83 ], more likely to be admitted emergently with longer hospital stays and more likely to require rehabilitation or nursing home care [ 16 •, 59 , 84 ]. Similarly, women with CLI have higher in-hospital mortality after both endovascular treatments and open surgery [ 85 ].…”
Section: Outcomes/prognosismentioning
confidence: 99%